In-service training of physician assistants in acute care in Ghana: Challenges, successes, and lessons learned - Anjali Niyogi; Barbra Villona; Beth L. Rubenstein; Stephanie J. Hubbard; Frank Baiden; Rachel T. Moresky (African Journal of Emergency Medicine, 2015)
To meet the greater demand for skilled personnel in Emergency Medicine (EM) in Ghana, the authors developed an in-service course in basic acute care for Physician Assistants (PAs) working in district hospitals. Methods: An initial training of trainers course was held for twenty-two PAs. From this initial group, ten were selected as Senior Trainers. Following a refresher course, Senior Trainers facilitated an in-service training and refresher course for other PAs from their regions. The course was organised into modules consisting of didactic lectures and interactive small group sessions. Assessment included testing, observation, case review, and simulations. Results: All groups showed improvement in knowledge. The majority learned information sequentially, inconsistently used physical examinations for diagnosis, and rarely reassessed following interventions. Practical skills were more easily acquired than clinical decision-making skills. The case discussions and simulations were the most helpful learning tools. Symptom-based algorithms were useful for daily practice. Conclusion: The greatest successes of this programme were providing the participants with greater confidence in basic life-saving skills and increasing their knowledge of and advocacy for EM. For continued success of this programme, a formal course with greater emphasis on filling Senior Trainer knowledge gaps, increased coordination with administrative authorities, and specific measurable clinical outcomes are needed.